2008
DOI: 10.2174/1874940200801010052
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Inactivation of Human Dipeptidyl Peptidases 8 and 9 by Oxidation

Abstract: Abstract:Hydrogen peroxide (H 2 O 2 ) can act as an intracellular messenger by oxidizing sulfhydryl groups in cysteines that can be oxidized at neutral pH. The oxidizing agents H 2 O 2 and pyrroloquinoline quinone and the large thiol reagents N-ethylmaleimide and 4-(hydroxymercuri) benzoate each inhibited dipeptidyl peptidase (DP) activity in the intracellular DPIV-related proteins DP8 and DP9 at pH 7.5. In contrast, these treatments did not alter activity in DPIV and fibroblast activation protein. Peptidase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 43 publications
1
59
1
Order By: Relevance
“…We have shown that DPP9 enzyme activity is reversibly inactivated by oxidation (31). An oxidative cellular environment created under oxidative stress or production of reactive oxygen species during cellular metabolism, such as growth factor stimulation, inhibits the PI3K/Akt pathway through inactivation of PTEN, a PtdIns(3,4,5)P3 phosphatase that antagonizes PI3K function (34).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that DPP9 enzyme activity is reversibly inactivated by oxidation (31). An oxidative cellular environment created under oxidative stress or production of reactive oxygen species during cellular metabolism, such as growth factor stimulation, inhibits the PI3K/Akt pathway through inactivation of PTEN, a PtdIns(3,4,5)P3 phosphatase that antagonizes PI3K function (34).…”
Section: Discussionmentioning
confidence: 99%
“…Extra-enzymatic functions of DPP8/DPP9 include cell adhesion, migration and apoptosis [57]. Interestingly, DPP8 and DPP9 are inactivated reversibly by H 2 O 2 oxidation involving two cysteines in each monomer [58]. To date, there are no crystal structures of DPP8 and DPP9 available.…”
Section: Dpp4 Gene Familymentioning
confidence: 99%
“…Mouse DPP8 and DPP9 enzymes have not been isolated for comparisons with their human counterparts in enzyme specificity and kinetics studies. Given that the crystal structures of DPP8 and DPP9 have not yet been solved, protein homology modeling has shown that DPP8 and DPP9 likely share a similar tertiary structure with DPPIV and FAP (32,33). DPP8 (34) and DPP9 (35) are dimeric, with each monomer likely consisting of an a/b-hydrolase domain and an 8 blade b-propeller domain and the active site of the peptidase locates at the interface of these 2 domains (Fig.…”
Section: Protein Modelmentioning
confidence: 99%
“…Therefore, it would be interesting to explore the consequences of SUMO1 interactions with DPP8 and DPP9. Furthermore, the activity of purified DPP9 from bovine testes (45) and recombinant DPP8 and DPP9 produced by insect cells (33) is dependent on the redox state of their cysteines, whereby enzyme activity is reversibly decreased by oxidation and increased by reduction (33).…”
Section: Dpp8 and Dpp9 Activity Regulationmentioning
confidence: 99%